Modeling the depth of chloride ingress and time-to-initiate rebar corrosion in concretes exposed to tiodal zone - Anacta, Ernesto Tan
Chloride -induced corrosion of steel in concrete is undoubtedly the most damaging type of deterioration faced by structures exposed to marine environment. In the Philippines where over 75% of the structures are located in this aggressive location, seawater-initiated corrosion had become a common problem to bridges, ports, and other near-shoreline structures, causing their deterioration and costing millions of pesos in terms of repair and maintenance every year.